SMERTENS APRIORI - OM PETER SLOTERDIJK OG HISTORIENS GENKOMST - Goldbæk, Henning (K&K - Kultur og Klasse, 2014)
THE A-PRIORI PAIN – AN ESSAY ON PETER SLOTERDIJK AND THE RETURN OF HISTORY | Sloterdijk’s claim, in Critique of Cynical Reason and in later books, that nobody knows, what it means to be modern, is related to the Hegelian tradition that still defines modern history as mythical history, and locates non-mythical history in a Utopian future. Sloterdijk’s late works, especially Spheres I-III, are an attempt to analyse the reasons, why modern individuals are still mentally living in the past and harmonic world of Plato’s ideas, Aristotle’s ethics and Plotin’s emanations, instead of accepting the fragmentarian world of modernity and globalization. And last but not least Sloterdijk’s books on Nietzsche are completely different from any other contemporary books on his philosophy. Nietzsche was the first modern thinker, who realized, that the death of God was the trauma of his time, and that it would take centuries to understand the full extent of the catastrophe, before we could even think of becoming modern. According to Sloterdijk we are still suffering from the a-priori Pain, we have only been modern for 100 years, since the First World War, and Sloterdijk’s hero is not the revolutionary, nor the left-wing student, but asceticism and the modern athlete, who lives from surpassing himself. Of course Sloterdijk is still longing for the return of history, but he keeps asking himself: The return of which history?